2021
DOI: 10.1002/adhm.202002142
|View full text |Cite
|
Sign up to set email alerts
|

Hemagglutinin Functionalized Liposomal Vaccines Enhance Germinal Center and Follicular Helper T Cell Immunity

Abstract: Despite remarkable successes of immunization in protecting public health, safe and effective vaccines against a number of life-threatening pathogens such as HIV, ebola, influenza, and SARS-CoV-2 remain urgently needed. Subunit vaccines can avoid potential toxicity associated with traditional whole virion-inactivated and live-attenuated vaccines; however, the immunogenicity of subunit vaccines is often poor. A facile method is here reported to produce lipid nanoparticle subunit vaccines that exhibit high immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…In this study, we prepared TQ-incorporated liposomes to increase the activity and decrease the toxicity of the drug. Phospholipids and cholesterol are safe and are commonly used in the preparation of liposomal antibiotics and vaccines [ 37 ]. Liposomes were prepared with DPPC and cholesterol to prepare TQ-loaded liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we prepared TQ-incorporated liposomes to increase the activity and decrease the toxicity of the drug. Phospholipids and cholesterol are safe and are commonly used in the preparation of liposomal antibiotics and vaccines [ 37 ]. Liposomes were prepared with DPPC and cholesterol to prepare TQ-loaded liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Modification of lipidbased nanoparticles with targeting ligands is a key strategy for efficiently targeting delivery systems into the lymph nodes or other desired tissues/cells. For example, Vu et al functionalized liposome surface with Hemagglutinin Antigen (HA) to improve antibody production efficiency [54]. This work showed that HA-functionalized liposome could cross the barrier cells in the lymph node and enhance germinal center formation and follicular helper T Cell Immunity.…”
Section: The Properties Of Lipid-based Nanoparticles Governing Their Efficienciesmentioning
confidence: 99%
“…The mature DC can express the antigenic proteins and present them on MHC class I and class II to CD8 + (cytotoxic) and CD4 + (helper) T cells respectively (adaptive immune response) [ 82 ]. Secreted antigen can be presented through the MHC II pathway to T helper cells and B cells, to generate memory B cells and plasma cells that can engender antigen-specific immune defenses and antibody production resulting in a durable protection [ 83 , 84 ]. Figure created using BioRender.com.…”
Section: Mrna Vaccines: An Emerging Vaccine Technologymentioning
confidence: 99%